1981
DOI: 10.1111/j.1399-3011.1981.tb02039.x
|View full text |Cite
|
Sign up to set email alerts
|

MODIFICATION OF LYSINE 69 REACTIVITY IN BOVINE GROWTH HORMONE BY CARBAMYLATION OF ITSN‐TERMINAL GROUP

Abstract: Bovine growth hormone was carbamylated under conditions that assure full reaction of the N‐terminal residue. Approximately 28% of lysine 179 and 7% of lysine 143 were also carbamylated. The modified hormone retained an important growth promoting activity and was as effective as the native hormone in competition assays in vivo for the receptors in rat liver. However, a change in its conformation must occur since lysine 69, which is resistant to trinitropheny‐ lation in the native hormone, reacted easily and und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Such changes can alter secondary and tertiary protein structures, leading to functional changes and resulting in molecular and cellular dysfunction (1,22,23). Studies have implicated carbamylation in changes in protein charge (24), conformation (25,26), stability (27), enzyme and hormone activity (28)(29)(30)(31)(32), binding properties (33)(34)(35), receptor-drug interaction (36,37), and cellular expression and responses (38)(39)(40)(41)(42)(43). For example, carbamylated collagen and LDLs accelerate the biochemical events of atherosclerosis (21,44,45), and carbamylated erythropoietin loses its activity (8,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…Such changes can alter secondary and tertiary protein structures, leading to functional changes and resulting in molecular and cellular dysfunction (1,22,23). Studies have implicated carbamylation in changes in protein charge (24), conformation (25,26), stability (27), enzyme and hormone activity (28)(29)(30)(31)(32), binding properties (33)(34)(35), receptor-drug interaction (36,37), and cellular expression and responses (38)(39)(40)(41)(42)(43). For example, carbamylated collagen and LDLs accelerate the biochemical events of atherosclerosis (21,44,45), and carbamylated erythropoietin loses its activity (8,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…26-28 Further research has capitalized on this finding, testing whether carbamylated erythropoietin may be used as a non-hematopoietic, tissue-protective agent in ischemic injuries. 29 Dozens of studies through the years have shown similar results implicating carbamylation in changes in protein charge, 30 conformation, 31,32 stability, 33 enzyme and hormone activity, 34-38 binding properties, 39-41 receptor-drug interaction 10,42 , and cellular expression and responses. 43-48 Lastly, tissue culture and animal model studies of the effects of carbamylated albumin have suggested that carbamylation gives albumin nephrotoxic and neutrophil-inactivating properties, providing further evidence that carbamylation of even a minor fraction of a normal protein may still confer significant pathogenic properties to the protein.…”
Section: Pathogenesismentioning
confidence: 93%
“…Unfortunately, only hGH and bGH have been extensively submitted to this kind of study. Careful examination of these results indicates that the region 128-160, where most of the /I-turns are found, also contains many residues highly reactive to hydrophilic reagents (47)(48)(49)(50)(51)(52), as was to be expected. Likewise, peptide bonds 132-133 in bGH and 147 and 149-150 in hGH are preferentially cleaved by proteolytic enzymes (53)(54)(55).…”
Section: Figurementioning
confidence: 63%